STUDI FITOREMEDIASI LOGAM TIMBAL (Pb) DAN KADMIUM (Cd) OLEH TANAMAN KAYAMBANG (Salvinia molesta) - Jacson Victor Morin; Darma Santi (FMIPA Universitas Papua, 2020)
Study phytoremediation of lead (Pb) and cadmium (Cd) by kayambang plants (Salvinia molesta) has been studied. This study assessed the ability of plants to absorb Pb and Cd which is influenced by the addition of various metal and NPK fertilizer on the medium containing the test solution. Samples of plants were interacted with NPK fertilizer, Pb and Cd. The variations of NPK 1 mg/L, I,5 mg/L, 2,5 mg/L and 10 mg/L and the variations of Pb (100 mg/L, 400 mg/L and 800 mg/L) and cadmium (50 mg/L, 100 mg/L and 200 mg/L). Optimum pH for growing the Kayambang plants (Salvinia molesta) is a range pH of 6-7. Observations were made every 7 days until the day of 35th, by measuring levels of Cd and Pb after the interaction of plants (roots, non-roots and growing media). The results showed that the Pb and Cd accumulation are higher at the root compared to non-root (stem and leaf). Effect of NPK fertilizer is very evident in the heavy plant where increasing levels of NPK fertilizer plant, the more heavy weight. The average value of FT in kayambang plants (Salvinia molesta)>1, then the plant can be used as a phytoremediator agent. The highest value FT of Pb is 11.22 and shown on condition [NPK] 10 mg/L, [Pb] 100 mg/L at day of 21th and for highest value FT of Cd is 9.57 and shown on condition [NPK] 10 mg/L, [Cd] 100 mg/L and day of 35th